2003
DOI: 10.1016/s0022-5223(03)01226-1
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic involvement of the radial artery in patients with coronary artery disease and its relation with midterm radial artery graft patency and endothelial function

Abstract: In coronary artery disease patients, radial artery atherosclerotic involvement is more frequent than that of the gold standard internal thoracic artery but still by far less severe than that of the common carotid artery. The early atherosclerotic signs often observed in the radial artery do not seem to have the potential to influence radial artery graft patency and endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Moreover, diabetes mellitus and renal dysfunction aggravate vascular wall morbidity [81,82]. According to Gaudino et al [83] atherosclerotic changes in the RA had little influence on the mid-term graft patency rate, whereas Ikeda et al [84] demonstrated postoperative accelerated intimal hyperplasia in RA grafts. However, although graft disease, meaning progressive atherosclerotic change, is a common situation as early as 5 years after surgery in SV grafts [85], no such situation is found in RA conduits [85,86].…”
Section: Ra Characteristicsmentioning
confidence: 99%
“…Moreover, diabetes mellitus and renal dysfunction aggravate vascular wall morbidity [81,82]. According to Gaudino et al [83] atherosclerotic changes in the RA had little influence on the mid-term graft patency rate, whereas Ikeda et al [84] demonstrated postoperative accelerated intimal hyperplasia in RA grafts. However, although graft disease, meaning progressive atherosclerotic change, is a common situation as early as 5 years after surgery in SV grafts [85], no such situation is found in RA conduits [85,86].…”
Section: Ra Characteristicsmentioning
confidence: 99%
“…Of note, no relationship seems to exist between irregularities of the RA at preoperative echographic evaluation and the angiographic patency when the artery is used as a CABG conduit [8].…”
Section: Histopathologymentioning
confidence: 95%
“…Optical coherence tomography provides an ideal method to screen for subtle intimal injury distributed heterogeneously within the vessel [20]. Measurements of luminal volume of the RA before and after harvest provide means for quantifying spasm with a high level of precision.…”
Section: Postoperative Radial Artery Spasm and Patencymentioning
confidence: 99%